2024
DOI: 10.1021/acs.jpcc.3c06707
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Cobalt-Phthalocyanines on Molybdenum Disulfide: Distinguishing between Single Crystals and Small Flakes

Philipp Haizmann,
Eric Juriatti,
Maren Klein
et al.

Abstract: Heterostructures consisting of transition metal dichalcogenides (TMDCs) and organic molecules are currently of enormous interest for a variety of applications. Comparably weakly interacting molecules, like phthalocyanines, exhibit a high potential for tuning the electronic properties of TMDCs. Knowledge of the molecular orientation is a prerequisite for understanding the nature and strength of the interfacial interaction. We study the molecular orientation of cobalt phthalocyanine (CoPc) and perfluorinated cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The displayed feature A represents transitions in states orthogonal to the molecular plane, while the B features are transitions within the molecular plane. The orientation of CoPc and CoPcF 16 on MoS 2 was extensively studied in a previous work . In summary, it can be said that the molecules adopt a flat, lying orientation relative to the MoS 2 surface.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The displayed feature A represents transitions in states orthogonal to the molecular plane, while the B features are transitions within the molecular plane. The orientation of CoPc and CoPcF 16 on MoS 2 was extensively studied in a previous work . In summary, it can be said that the molecules adopt a flat, lying orientation relative to the MoS 2 surface.…”
Section: Resultsmentioning
confidence: 93%
“…One aspect that must be considered is the possibility that the orientation of molecules relative to the MoS 2 surface may vary, which can influence substrate–molecule interactions . In previous, more detailed X-ray absorption studies, it was demonstrated that in CoPc­(F 16 ), a flat, face-on orientation is adopted on MoS 2 …”
Section: Resultsmentioning
confidence: 99%
“…Such an increase in the resistance is detrimental to the RC time and the expected response time. In a similar context, Haizmann et al have recently shown that substrate roughness and its effect on thin TMDC layers also alter the orientation of small molecules adsorbed to the TMDC surface . While the exact consequences of this alteration remain to be explored, it is likely that this will affect the chemical interactions at the interface and, thus, the efficiency with which such small molecules saturate surface defects.…”
Section: Speed-limiting Factors To the Extrinsic Photoresponsementioning
confidence: 99%